Changes in the distribution of the tear film lipid layer after intensive pulsed light combined with meibomian gland expression in patients with meibomian gland dysfunction - Yongwoo Lee; Sung Woo Lee; Ji Kyu Yun; So Young Han; Chul Young Choi (PLoS ONE, 2025)
Purpose This study aimed to investigate changes in dry eye disease (DED) parameters and tear film lipid layer distribution after intensive pulse light (IPL) combined with meibomian gland expression (MGX) in patients with meibomian gland dysfunction (MGD). Methods This retrospective study included 218 patients diagnosed with MGD who underwent IPL combined with MGX. Various DED parameters, including tear film lipid layer thickness (LLT), were measured using a Placido disc tear film analyzer and slit lamp. Inferior corneal images were quantified and divided into upper, lower, nasal, and temporal quadrants, with further subdivision into six parts from top to bottom using Python. Results The ocular surface disease index, meibomian gland expressibility, and quality scores significantly improved after three treatment sessions. Slit-lamp-measured DED parameters also improved, excluding the fluorescein-stained tear meniscus height. Redness in the nasal limbal and bulbar conjunctivae significantly decreased. The mean LLT tended to increase after treatment. LLT in the upper half of the images, but not in the lower half, increased significantly, with the difference in LLT between the two halves decreasing significantly from 34.46 ±  15.73 to 30.27 ±  14.63 nm (p =  0.031). When the vertical distribution was analyzed by further subdivision into six equal parts from top to bottom, the average difference in LLT decreased in the uppermost segment after treatment. Conclusion IPL combined with MGX reduced the vertical distribution of lipids in patients with MGD by reducing lower tear film lipid layer stasis. Thus, the Placido disc tear film analyzer is a useful tool for analyzing lipid layer distribution in MGD.